2012
DOI: 10.48550/arxiv.1203.4240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dark matter concentrations and a search for cores in Milky Way dwarf satellites

Abstract: We investigate the mass distributions within eight classical Milky Way dwarf spheroidal galaxies (MW dSphs) using an equilibrium Jeans analysis and we compare our results to the mass distributions predicted for subhalos in dissipationless ΛCDM simulations. In order to match the dark matter density concentrations predicted, the stars in these galaxies must have a fairly significant tangential velocity dispersion anisotropy (β ≃ −1.5). For the limiting case of an isotropic velocity dispersion (β = 0), the classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Subsequent numerical results find haloes with steep inner density slopes and NFW or Einasto profiles (Dekel, Devor, & Hetzroni 2003a;Dekel et al 2003b;Reed et al 2005;Diemand et al 2008;Springel et al 2008;Navarro et al 2010). In contrast, observations have repeatedly found constant density 'cores,' where α ∼ 0 (de Blok et al 2001;de Blok & Bosma 2002;Swaters et al 2003;Strigari et al 2006;Walker et al 2009;Strigari, Frenk, & White 2010;Oh et al 2011;Walker & Peñarrubia 2011;Hayashi & Chiba 2012;Wolf & Bullock 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Subsequent numerical results find haloes with steep inner density slopes and NFW or Einasto profiles (Dekel, Devor, & Hetzroni 2003a;Dekel et al 2003b;Reed et al 2005;Diemand et al 2008;Springel et al 2008;Navarro et al 2010). In contrast, observations have repeatedly found constant density 'cores,' where α ∼ 0 (de Blok et al 2001;de Blok & Bosma 2002;Swaters et al 2003;Strigari et al 2006;Walker et al 2009;Strigari, Frenk, & White 2010;Oh et al 2011;Walker & Peñarrubia 2011;Hayashi & Chiba 2012;Wolf & Bullock 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Determining precise and robust mass profiles is challenging, particularly if the goal is to separate the dark and baryonic components. Low surface brightness and dwarf spheroidal galaxies are often considered ideal targets for DM studies, since the mass fraction of baryons is minimal, and observations indicate that many of these galaxies have a DM core rather than the expected cusp (e.g., Simon et al 2005;de Blok et al 2008;Wolf & Bullock 2012). Due to their shallow potential wells, however, these are fragile systems and may be disrupted by supernovae (see references above).…”
Section: Introductionmentioning
confidence: 99%
“…The cold dark matter (CDM) paradigm (Blumenthal et al 1984) works extremely well on large scales (Seljak et al 2005;Percival et al 2007;Ferramacho et al 2009;Sánchez et al 2009;Komatsu et al 2011), but there remains the possibility of deviations from the CDM expectations on small scalesarising notably from the issue of cores vs. cusps and the inner slope of dark matter density profiles (Salucci 2001;Donato et al 2004;Newman et al 2009;Donato et al 2009 Newman et al 2011;Salucci et al 2012;Wolf & Bullock 2012) and the apparent paucity of bright satellites around the Milky Way (Boylan-Kolchin et al 2011, 2012. Several extensions to dark matter phenomenology E-mail: abenson@obs.carnegiescience.edu (Markevitch et al 2004;Boehm & Schaeffer 2005;Ahn & Shapiro 2005;Miranda & Macciò 2007;Randall et al 2008;Boyarsky et al 2009;Lovell et al 2012) and several different particle physics candidates for dark matter (Raffelt 1990;Turner 1990;Jungman et al 1996;Hogan & Dalcanton 2000;Spergel & Steinhardt 2000;Abazajian et al 2001;Cheng et al 2002;Feng et al 2003;Sigurdson & Kamionkowski 2004;Hubisz & Meade 2005;Feng et al 2009) have been put forward to explain these deviations, although it remains unclear if any of these proposals is able to fully explain observed phenomena (Kuzio de Naray et al 2010) or if they are even necessary, with the observed phenomena simpl...…”
Section: Introductionmentioning
confidence: 99%